2009
DOI: 10.1074/jbc.m109.023044
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Adapter-like (Mal)/TIRAP Interaction with TRAF6 Is Critical for TLR2- and TLR4-mediated NF-κB Proinflammatory Responses

Abstract: Toll/interleukin-1 (TIR)receptor-containing adapters are critical in orchestrating the different signal transduction pathways following Toll-like receptor (TLR) activation. MyD88 adapter-like (Mal), also termed TIRAP, is involved in bridging MyD88 to the receptor complex for TLR-2 and TLR4 signaling in response to bacterial infection. We have previously reported an interaction between Mal and tumor necrosis factor receptor-associated factor 6 (TRAF6) via a TRAF6-binding motif, the disruption of which inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(142 citation statements)
references
References 33 publications
5
136
0
1
Order By: Relevance
“…In addition to acting through AP-1 transcription factors, p38-MAPK promotes mRNA stabilization, influences NF-B activity, modulates gene expression by regulating chromatin modifiers, and directly influences protein translation downstream of inflammatory stimuli (25,31,(65)(66)(67)(68)(69). Further studies will be required to define which of these many different p38-MAPK-dependent mechanisms are responsible for TLR2 signaling in ECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acting through AP-1 transcription factors, p38-MAPK promotes mRNA stabilization, influences NF-B activity, modulates gene expression by regulating chromatin modifiers, and directly influences protein translation downstream of inflammatory stimuli (25,31,(65)(66)(67)(68)(69). Further studies will be required to define which of these many different p38-MAPK-dependent mechanisms are responsible for TLR2 signaling in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the canonical NF-B pathway results in the degradation of bound IB␣, IB␤, or IB⑀ in the cytoplasm, which leads to the translocation of NF-B to the nucleus to mediate transcriptional events (22,23). Proinflammatory stimuli can also induce the transactivation of p65 through phosphorylation, such as occurs after the TLR2-dependent activation of macrophages (24,25). The MAPK family members p38-MAPK, JNK, and ERK1/2 participate in the inflammatory response and are induced by TLR2 activation in macrophages (26 -28).…”
mentioning
confidence: 99%
“…Cell (33) and display decreased TNF␣ production upon LPS or Pam2 stimulus (32). We previously transduced these immortalized macrophages with wild-type Mal, which increases their responsiveness toward TLR4 and TLR2 ligands (31,34).…”
Section: Methodsmentioning
confidence: 99%
“…4D, first and second panels). Studies have shown that Mal and TRAF6 directly interact in response to TLR4 stimulation (48,49), and hence the effect of A46 on the Mal-TRAF6 interaction was also assessed. Similar to the case for MyD88:IRAK2 and Mal:IRAK2, the Mal: TRAF6 interaction was unimpaired by A46 (Fig.…”
Section: -C) Lps-induced Activation Of the Rantes (Ccl5) And Ifn-␤ Pmentioning
confidence: 99%